Grouping of Misconduct Types in Case of VAT Fraud - Szabó, Barna (Magyar Rendészet, 2019)
The formation of the tax system is as old as the emergence of statehood, together with the intention of not paying taxes. The value added tax, i.e. VAT, is no difference. The European Communities decided to introduce VAT during the tax harmonisation process in 1973. The liberalised free flow of production factors between Member States has provided an opportunity for the increasingly complicated and complex methods of VAT fraud. The main objective of my study is to present a possible grouping of VAT frauds according to my own conceptual approach.